Connecting Polygons to Coding (pp. 25–33) - Klovekorn, Allyson (Ohio Journal of School Mathematics, 2019)
This paper discusses a lesson implemented in a high school classroom that promotes the connection of geometry–specifically, polygons—to coding using freely available, web-based programming tools. Details of the lesson and the tools (i.e., Turtle graphics / Logo) are shared as well as a discussion of revisions based upon relevant literature and conversations with colleagues.